2013
DOI: 10.3329/cujbs.v4i1.13398
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics of the cyprinid fish, Amblypharyngodon mola (Hamilton) from the Kaptai lake, Bangladesh

Abstract: Length frequency based population dynamics of the small indigenous cyprinid fish, Amblypharyngodon mola from the Kaptai lake (an artificial water reservoir), Bangladesh were studied using the computer based FiSAT program. Growth parameters La and K were found to be 104.65 mm and 0.95 year-1 respectively. The annual rate of natural mortality (M), fishing mortality (F) and total mortality (Z) were found to be 1.22, 2.04 and 3.26 respectively. Exploitation rate (E) was 0.63, while maximum yield per-recruit (Emax)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
3
1
Order By: Relevance
“…According to the Powell-Wetherall plot, L ∞ values were noted as 7.47 to 7.52, 7.13 to 7.15 and 7.38 to 7.47 cm, while Z/K values varied from 0.812 to 1.125, 0.934 to 1.09 and 0.979 to 1.295 for the female, male and com-bined sexes of D. devario respectively (Figure 2). Azadi and Mamun (2009) observed that values of L ∞ and Z/K recorded as 10.338 and 3.310 cm for A. mola were relatively higher than the present fish species for their taxonomic variations.…”
Section: Figurecontrasting
confidence: 54%
See 1 more Smart Citation
“…According to the Powell-Wetherall plot, L ∞ values were noted as 7.47 to 7.52, 7.13 to 7.15 and 7.38 to 7.47 cm, while Z/K values varied from 0.812 to 1.125, 0.934 to 1.09 and 0.979 to 1.295 for the female, male and com-bined sexes of D. devario respectively (Figure 2). Azadi and Mamun (2009) observed that values of L ∞ and Z/K recorded as 10.338 and 3.310 cm for A. mola were relatively higher than the present fish species for their taxonomic variations.…”
Section: Figurecontrasting
confidence: 54%
“…Zakeyuddin et al (2017) found that L ∞ values were 10.90 cm, which is comparatively higher than the present value, which might be due to the geographical variation, whereas the Ø value was 2.15 for D. regina from the Sungai Kerian Basin in Malaysia, which is close to the present findings. Azadi and Mamun (2009) also estimated the asymptotic length (L ∞ ) for Amblypharyngodon mola as 10.465 cm and the Ø as 4.017, which were higher than D. devario and may be due to different taxa. The growth coefficient (K) of D. devario varied from 0.78 to 1.8 year -1…”
Section: Length-based Growth Patterns 341 Assessment Of Growth Indicesmentioning
confidence: 97%
“…There have been some works focusing on the limnological and biological aspects of the reservoir [ 20 , 21 ], biodiversity conservation [ 22 , 23 ]. Some studies have also been done on population dynamics[ 19 , 24 , 25 , 26 ]; and ecosystem functions [ 27 , 28 ]. Yet, no work has been done to estimate the biological reference points (BRPs) of these two fish stocks from the Kaptai reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…In Bangladesh population dynamics of several fishes have been done by many authors such as Mustafa and Khan (1988), Azadi et al ( , 1996Azadi et al ( , 1997, Azadi and Quddus (1995), Azadi and Barua (1999), Mustafa and Azadi (1995), Azadi (2000), Azadi andMamun (2009), andSarkar et al (2017). However, studies on population dynamics of mullets, especially of Rhinomugil corsula, has not been done yet in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%